2012
DOI: 10.3171/2011.12.focus11318
|View full text |Cite
|
Sign up to set email alerts
|

Failed epilepsy surgery for mesial temporal lobe sclerosis: a review of the pathophysiology

Abstract: Object The object of the current study was to review the electrophysiology and pathological substrate of failed temporal lobe surgery in patients with mesial temporal sclerosis. Methods A systematic review of the literature was performed for the years 1999–2010 to assess the cause of failure and to identify potential reoperation candidates. Results Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 52 publications
(79 reference statements)
0
21
0
Order By: Relevance
“…Mesial temporal sclerosis is the most common preoperative diagnosis in adults undergoing epilepsy surgery, and its results stand as a de facto gold standard for assessing surgical seizure outcomes. A recent review 35 of large modern studies revealed overall Engel Class I outcomes in 541 (78.9%) of 686 patients who had undergone surgery for this condition. Resection is, in general, somewhat more successful than other epilepsy operations, such as hemispherectomy 25 for Rasmussen encephalitis (about 70% Engel Class I), SturgeWeber syndrome (same), or hemimegalencephaly (approximately 50% Engel Class I).…”
Section: Nononcological Perspectivementioning
confidence: 99%
“…Mesial temporal sclerosis is the most common preoperative diagnosis in adults undergoing epilepsy surgery, and its results stand as a de facto gold standard for assessing surgical seizure outcomes. A recent review 35 of large modern studies revealed overall Engel Class I outcomes in 541 (78.9%) of 686 patients who had undergone surgery for this condition. Resection is, in general, somewhat more successful than other epilepsy operations, such as hemispherectomy 25 for Rasmussen encephalitis (about 70% Engel Class I), SturgeWeber syndrome (same), or hemimegalencephaly (approximately 50% Engel Class I).…”
Section: Nononcological Perspectivementioning
confidence: 99%
“…Reoperation with conventional surgery for the TLE remnant can obtain a seizure outcome rate ranging from 50% to 60%. 1,7,17,22,24 However, considering the invasiveness and comparable surgical outcomes of the conventional reoperation in those who underwent a failed temporal lobectomy, our present results suggest that GKRS can be considered an alternative treatment to open cranial reoperation in patients with MTLE-HS who had residual or recurrent seizures after ATL-AH.…”
Section: Discussionmentioning
confidence: 91%
“…22 Of these causes, incomplete resection of mesial structures is a potent and major cause of surgical failure. Although reoperation may be beneficial in highly selected patients with MTLE-HS, several reports have argued that 52%-63% of patients could be seizure free after reoperation (extension of the cortical resection along the surgical scar) for TLE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Among patients with MTLE and mesial temporal sclerosis, surgery reduced seizures for approximately 75%. 3,12,19,23 Although this surgery is considered safe and effective, it is not free of complications. Surgical intervention has changed and will continue to change for the foreseeable future because of advances in neuroimaging, neuronavigation, and anesthesia.…”
Section: Discussionmentioning
confidence: 99%